Decadal changes in glacier parameters in the Cordillera Blanca, Peru, derived from remote sensing - Racoviteanu, Adina E. (2008)
Original abstract: We present spatial patterns of glacier fluctuations from the Cordillera Blanca, Peru, (glacier area, terminus elevations, median elevations and hypsography) at decadal timescales derived from 1970 aerial photography, 2003 SPOT5 satellite data, Geographic Information Systems (GIS) and statistical analyses. We derived new glacier outlines from the 2003 SPOT images, and ingested them in the Global Land and Ice Measurements from Space (GLIMS) glacier database.We examined changes in glacier area on the eastern and western side of the Cordillera in relation to topographic and climate variables (temperature and precipitation). Results include (1) an estimated glacierized area of 569.6 21 km2 in 2003, (2) an overall loss in glacierized area of 22.4% from 1970 to 2003, (3) an average rise in glacier terminus elevations by 113m and an average rise in the median elevation of glaciers by 66 m, showing a shift of ice to higher elevations, especially on the eastern side of the Cordillera, and (4) an increase in the number of glaciers, which indicates disintegration of ice bodies. Annual air temperature showed a significant upward trend in the last 30 years, with larger temperature increases at lower elevations. There was a slight but not significant decrease in precipitation. Our results are consistent with glacier retreat and warming trends noted in the last three decades in the tropics.